ВЗАИМОСВЯЗЬ ЛИЧНОСТНЫХ ОСОБЕННОСТЕЙ С ЦЕННОСТНЫМИ ОРИЕНТАЦИЯМИ СТУДЕНТОВ-ПСИХОЛОГОВ - Нурымбетова, Э.Ж. (SCIENCE and SOCIETY, 2025)
The article deals with the influence of personality traits on value orientations of psychology students. The relevance of the study is emphasized by the importance of professional and personal qualities for the success of professional activity of psychologists as specialists.
Keywords: extraversion; benevolence; conscientiousness; neuroticism; openness to experience; tradition; autonomy; security